Analysis of the Application of Sharia Principles and Service Quality on Consumer Decisions to Stay at Hotel Syariah - Mutiara Eka Putri; Tulus Suryanto; Hanif Hanif (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2023)
The demands of tourists to obtain Sharia-compliant hotel facilities and services have encouraged hoteliers to develop Sharia hotel concepts. This research aims to analyze the influence between the application of Sharia principles and service quality on consumers' decisions to stay at Sharia hotels. Quantitative research methods were used to collect data through surveys of consumers who had remained at the Syariah Rossa Ono Hotel, West Lampung Regency. The data obtained was analyzed using appropriate statistical techniques to understand the influence of the application of sharia principles and service quality on consumer decisions. The results of the analysis show that the application of Sharia principles and service quality have a significant influence on consumers' decisions to choose to stay at a Sharia hotel (p value = 0,000). The implication of this research is the importance of Sharia hotels to pay attention to and improve the application of Sharia principles and service quality to increase consumer attractiveness and trust. This study contributes to understanding the factors that influence consumer preferences in the context of Sharia hotels. It directs the hotel industry to increase its competitiveness in a competitive market.